Espécies frutíferas nativas dos cerrados de Goiás: caracterização e influências do clima e dos solos - Naves, Ronaldo Veloso (1999)
Native fruit species represent an important role in the Brazilian State of Goiás. Due to the limited scientific knowledge on these species, the current work aimed the characterization of plants, soil and climate, with their inter-relationships for five Goiás-native fruit trees present in the cerrado (a type of Brazilian savanna) with potential for economic exploration. Studied fruit trees were: araticum (Annona crassíflora Mart.), caju-arbóreo-do-cerrado (Anacardium othonianum Rizz.), cagaita (Eugenia dysenterica D.C.), mangaba (Hancomia speciosa Gomez) and pequi (Caryocar brasiliense Camb.). Thirty seven Goiás cities were covered in about 200000 km2 , between 14° 31' 5.48" and 18° 44' 51.64" South Latitude and 47° 46' 13.95" and 52° 39' 53.42" West Longitude. Fifty sampling areas with 1 ha each were divided in four 0.25 ha quarters. At least one selected fruit tree was present in the chosen cerrado area, with the lowest possible human action. Area, plant and soil till 80 cm deep features were statistically analyzed and the results showed that E. dysenterica trees are distributed in a more gathered pattem, whereas A. crassfflora and mainly C. brasiliense trees are amply dispersed among Goiás cerrado. The studied species are generally short in size, present small basal area and show canopy shape varying from global on A. othonianum and C. brasiliense and columnar on E. dysenterica and A. crassiflora trees. Strong light competition is very frequent among these species. Greater densities are present in higher altitude areas with lower average annual temperatures. A. crassiflora and E. dysenterica trees are xxii more frequent in soil "Latossolo Vermelho Amarelo", while C. brasiliense and A. othonianum present higher densities on soil "Litossolo". Studied species show survival strategies that give them establishment and development ability on extremely soil-nutrient poor environments, with high toxic aluminum levels. Even in those conditions, leaf levels of nutrients are adequate. A. crassiflora and C. brasiliense trees tend to occur in soils with lower levels of potassium, calcium, magnesium and zinc when compared with soils where these species do not occur. E. dysenterica trees tend to occur in soils with potassium, calcium, magnesium, manganese and clay in higher levels than areas where the species is not present. A. othonianum and C. brasiliense densities increases with highest acidity and ~ basal area oi this frui! trees increases with lowest aluminum saturation. E.\~ dysenterica tree densities decrease with the increase of foliar leveis of potassium, while A. crassiflora tree densities decreases with foliar calcium increase. A. othonianum height is increased with the increment of foliar leveis of zinc, whereas C. brasiliense trees are taller when potassium and manganese are increased on the leaf. Areas with natural occurrence of the studied fruit trees are suffering an intense human action.